SEROPREVALENCIA DE Neospora caninum EN BOVINOS LECHEROS CRIADOS AL PASTOREO EN LA PROVINCIA DE MELGAR, PUNO - Atoccsa H., José (2005)
The aim of the current study was to assess the seroprevalence of Neospora caninum in grazing dairy cattle in the province of Melgar, Puno, through serum antibody detection using the immunofluorescence indirect technique (IFI). A total of 419 sera was obtained from seven herds. The seroprevalence varied from 4.0 ± 7.7% to 37.5 ± 11.9%, while the overall prevalence was 18.1 ± 3.7%, which was considered moderate. All herds showed at least one positive animal. Age and location showed to be a risk factor in the prevalence of the infection.